PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS IV SD GP TOKIN - Tuerah, Roos M. S.; Rorimpandey, Widdy H. F.; Aseng, Ekklesia (DIKSAR : Jurnal Pendidikan Dasar, 2023)
This study aims to improve students' science learning outcomes on cycle material in class IV SD GP TOKIN after the application of the Problem Based Learning (PBL) learning model. The research method used is classroom action research (PTK) which consists of 2 cycles, each research cycle consists of 4 (four) stages, namely planning, action, observation and reflection. The subjects of this study were fourth grade students of SD GP TOKIN with a total of 17 students consisting of 10 boys and 7 girls. The results showed that cycle I reached a completeness of 52.94%, then increased in cycle II to reach 100% completeness. In addition, the average value of learning outcomes also increased from cycle I of 67.64 increased in cycle two to 85.58. In accordance with the formulation of the problem, it can be concluded that the application of the PBL learning model can improve the learning outcomes of science cycle material in class IV SD GP Tokin